Patisserie, planche - Pastry, historical, line illustrations, baking... - EN NOIR & BLANC (Wikimedia Commons, 2013)
Notice iconographique issue de Wikimedia Commons. Titre: Patisserie, planche - Pastry, historical, line illustrations, baking and baked food in France, etc. - Public domain illustration from Larousse du XXme sicle 1932. Patisserie, planche - Pastry, pastries, historical, line illustrations, baking and baked food in France, etc. - Public domain illustration from Larousse du XXme sicle 1932 ditions Larousse is a French publishing house specialising in reference works such as dictionaries. It was founded by Pierre Larousse and its best-known work is the Petit Larousse.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie